Effect of Shear Flow on Crystallization of Sydiotactic Polypropylene/Clay Composites - Ahmad, N.; Fouad, E.; Ahmad, F. (Engineering, Technology & Applied Science Research, 2018)
The high sensitivity of crystallization to shear flow is a subject of great research interest the last several years. A set of syndiotactic polypropylene/clay composite samples were used to examine the effect of shear flow on crystallization kinetics. This phenomenon alters both processing and material final properties. In the present work, the effects of clay contents and shear flow on the rate of flow induced crystallization were investigated using rheological technique. Small amplitude oscillatory shear experiments were performed using advanced rheometric expansion system (ARES). The crystallization rate is found to alter by both shear and clay contents in the polymer composites.